BCAAs and related metabolic enzymes: partners in crime driving tumor development - He, Binfan; Li, Lingxi; Liu, Ye; Hao, Mengmeng; Zhang, Ling; He, Rongzhang (Frontiers in Cell and Developmental Biology, 2026)
Metabolic reprogramming of Branched-chain amino acids (BCAAs)-leucine, isoleucine, and valine-has emerged as a constitutive feature of cancer, extending far beyond their canonical roles in protein synthesis and energy provision. In malignancy, these essential amino acids function as pivotal signaling mediators and epigenetic modulators, thereby propelling tumor progression, facilitating immune evasion, and conferring resistance to therapeutic agents. This review delineates how cancer cells subvert branched-chain amino acid metabolism to fuel anabolic processes, activate oncogenic signaling cascades including mTOR and PI3K/AKT, and remodel the tumor microenvironment. A framework is presented to categorize the differential reliance of various cancers on key catabolic enzymes-BCAT1, BCAT2 and BCKDK-underscoring their therapeutic vulnerability. The paradoxical role of BCAAs in modulating anti-tumor immunity is examined alongside the potential of dietary modulation and the development of pharmacological inhibitors targeting this pathway. Concluding perspectives highlight the trajectory for translating these insights into precision oncology, advocating for biomarker-guided and context-specific therapeutic strategies.